2017
DOI: 10.1111/vec.12671
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of albumin, colloid osmotic pressure, von Willebrand factor, and coagulation factors in canine cryopoor plasma, cryoprecipitate, and fresh frozen plasma

Abstract: The mean albumin concentration and COP were highest in CPP, suggesting that CPP may be a potential alternative to FFP for oncotic support and albumin replacement. CRYO contained higher activities of vWf and factor VIII than other products and could be used to treat vWf deficiency and hemophilia A. As vitamin K dependent coagulation factors II, VII, and X in CPP were similar to FFP, CPP may be an option for replacement of most of vitamin K dependent factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
(32 reference statements)
1
28
1
Order By: Relevance
“…There are limited published data on the use of CPP in people, but it may be used in lieu of FFP for treatment of disseminated intravascular coagulation and for plasma exchange in cases of thrombotic thrombocytopenic purpura . In veterinary medicine, some suggest CPP for use in hypoalbuminemic patients and for treatment of vitamin K antagonist rodenticide toxicity, although until a previous study by our group, no published data on the content of CPP existed . Our study showed that CPP contains higher concentrations of albumin and has a higher COP than FFP, supporting its use as a potential treatment option for hypoalbuminemia.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…There are limited published data on the use of CPP in people, but it may be used in lieu of FFP for treatment of disseminated intravascular coagulation and for plasma exchange in cases of thrombotic thrombocytopenic purpura . In veterinary medicine, some suggest CPP for use in hypoalbuminemic patients and for treatment of vitamin K antagonist rodenticide toxicity, although until a previous study by our group, no published data on the content of CPP existed . Our study showed that CPP contains higher concentrations of albumin and has a higher COP than FFP, supporting its use as a potential treatment option for hypoalbuminemia.…”
Section: Discussionsupporting
confidence: 51%
“…This is not surprising, given that HES has a higher oncotic pressure than plasma . A previous study reported HES 6% 670/0.75/4:1 to have a COP of 32.7 mm Hg, while our previous study found the COP of CPP to be 14.5 mm Hg . Given this large difference in COP between the 2 products, whatever COP benefit may have been gained by the increase in albumin was likely overshadowed by the COP influence of HES.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations